Parallelotopia: Ottoman transcultural memory assemblages in contemporary art practices from the Middle East. (October 2019) - Koureas, Gabriel
This article engages with the conversations taking place in the photographic space between then and now, memory and photography, and with the symbiosis and ethnic violence between different ethnic communities in the ex-Ottoman Empire. It questions the role of photography and contemporary art in creating possibilities for coexistence within the mosaic formed by the various groups that made up the Ottoman Empire. The essay aims to create parallelotopia, spaces in the present that work in parallel with the past and which enable the dynamic exchange of transcultural memories. Drawing on memory theory, the article shifts these debates forward by adopting the concept of 'assemblage'. The article concentrates on the aesthetics of photographs produced by Armenian photographic studios in Istanbul during the late nineteenth century and their relationship to the present through the work of contemporary artists Klitsa Antoniou, Joanna Hadjithomas, Khalil Joreige and Etel Adnan as well as photographic exhibitions organised by the Centre for Asia Minor Studies, Athens, Greece.